Making newsworthy news: The integral role of creativity and verification in the human information behavior that drives news story creation. (19th March 2022) - Gutierrez Lopez, Marisela; Makri, Stephann; MacFarlane, Andrew; Porlezza, Colin; Cooper, Glenda; Missaoui, Sondess
Abstract: Creativity and verification are intrinsic to high‐quality journalism, but their role is often poorly visible in news story creation. Journalists face relentless commercial pressures that threaten to compromise story quality, in a digital era where their ethical obligation not to mislead the public has never been more important. It is therefore crucial to investigate how journalists can be supported to produce stories that are original, impactful, and factually accurate, under tight deadlines. We present findings from 14 semistructured interviews, where we asked journalists to discuss the creation of a recent news story to understand the process and associated human information behavior (HIB). Six overarching behaviors were identified: discovering, collecting, organizing, interrogating, contextualizing, and publishing . Creativity and verification were embedded throughout news story creation and integral to journalists' HIB, highlighting their ubiquity. They often manifested at a micro level; in small‐scale but vital activities that drove and facilitated story creation. Their ubiquitous role highlights the importance of creativity and verification support being woven into functionality that facilitates information acquisition and use in digital information tools for journalists.